ANALISIS KETERAMPILAN MENULIS SURAT RESMI MAHASISWA PGSD UNIVERSITAS RIAU - Fauziatul Husni; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is a descriptive quantitative research done to see the skills of PGSD students of Universitas Riau in writing official letter. Data collection techniques in the form of student test results to write an official letter.The validity of his research has been validated by the expert. The sample in this research are 162 students of class of 2014 and 2015 students of PGSD Universita Riau.Skills of PGSD students of Universitas Riau after analyzed by using categories, from 11 aspects that have been determined, get the result that on aspect of letter head average 44,65 with less category, aspects of a good category letter date with an average of 72.43,aspects of letter numbers with less category with an average of 31.48,on the attachment aspect of the category is very good with an average of 99.38, on the aspect of the subject of good category with an average of 80.86,on the aspect of the category sender is enough with an average of 65.06, on the aspect of the opening categorical category enough with an average of 68.31,on aspects of good category letter content with an average of 70.58,on the aspect of the less closing category cover with an average of 27.78,on the category sender aspects enough with an average of 68.64.And on the aspect of using a category sentence enough with an average of 63.95,From these results, the overall average of 63,021 is obtained with sufficient category, it indicates that the skills of PGSD Universitas Riau students are quite skilled.Key Words : Official Letter